Application of CAMEL rating strategy to make a comparison of IPDC Finance Ltd.’s performance to one of its key competitors - Piya, Ayesha Aktar (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.